Recent trends in MPLS networks: Technologies, applications and challenges - Ridwan M.A.; Radzi N.A.M.; Wan Ahmad W.S.H.M.; Abdullah F.; Jamaludin M.Z.; Zakaria M.N. (Institution of Engineering and Technology, 2023)
Electric power transmission networks; Multiprotocol Label Switching; Differentiated Services; Network flexibility; Network latencies; Network provider; Optimal performance; Packet-based networks; Protection and restoration; Traffic Engineering; Quality of service